Variations of Macro-compounds in Cyanobacterium, Thermosynchococcus elongatus CL-1 Under Various Nutrients - Ko, Tzuhsing; Hsueh, Hsinta (Asian Journal of Chemistry, 2015)
The photosynthetic algae, Thermosynchococcus elongatus CL-1 (TCL-1) purified from an alkaline hot spring (pH 9.3, 62 °C) in eastern Taiwan was applied to enhance the overall CO2 absorption capacity in aqueous solution. It was observed that the Thermosynchococcus elongatus CL-1 can be experimentally cultivated over pH 12 and suggested its high affinity of bicarbonate and adapted ability of alkaline condition. A series of the variations of macro-compounds, including lipids, carbohydrates, proteins, pigments and element compositions (C, H and N) were determined under a batch cultivation at pH 9. Additionally, a combined method with Fourier transform infrared spectrum and curve fitting as well as a wet chemistry method was used to determine the variations of lipids.